Exclusive breastfeeding behavior among mothers aged - Anur Rahima Sari; Niken Meilani; Tri Maryani (Jurnal Kesehatan Ibu dan Anak, 2019)
The number of adolescent pregnancies in Indonesia was still high. This study aimed to find out the exclusive breastfeeding behavior among mothers aged <20 years old. This study was a quantitative used cross-sectional approach. The sample in this study was mothers aged <20 years who had babies aged 6-24 months in Karangmojo, Semanu, Semin, Gunung Kidul Regency in 2019. Minimal sample calculation by Lemeshow was 45 respondents. Data collected by a structured questionnaire. Data analysis involved univariate, bivariate analysis using the chi-square test and fisher's exact test, while multivariate analysis used logistic regression. The results showed that 75.5% of adolescent mothers aged <20 years old practice exclusive breastfeeding. Bivariate analysis showed that occupational factors (p-value = 0.001), parity (p-value = 0.001), pregnancy status (p-value = 0.010), family support (p-value = 0.002) and husband support (p-value = 0.003) were correlated to exclusive breastfeeding. Multivariate analysis showed husband support (p-value = 0.005; OR = 26.591). Husband support as the most influential factor to exclusive breastfeeding behavior among mothers <20 years old